Trace Metals Content Of The Sewage From The Sewer Network Of Abidjan (Côte d’Ivoire) - Yves, Gnagne Agnes Essoh Jean Eudes; Bernard, Yapo Ossey; Jeanne, Ohou-Yao Marie; Meite, Ladji; Nicaise, Ballet Tiama Guy; Veronique, Mambo (European Scientific Journal, ESJ, 2016)
Many studies have incriminated the effluents of the sewer network of Abidjan as major trace metal contamination sources in the Ebrié Lagoon. However, no data are available on wastewater regarding trace metal contaminations in Cote d’Ivoire. Thus, this study aimed at assessing the level of contamination of wastewater by metals copper, iron, cadmium, lead and Zinc. To achieve this objective, six campaigns were carried out from december 2013 to november 2014 in eight specific sites. The samples were analyzed using an atomic absorption spectrophotometer AA20 Varian, after mineralization. The results showed a significant contamination of effluents from the sewer network. The order of metals concentrations was Fe >Zn > Cu> Pb>Cd. Total metal concentrations (μg/L) ranged from 313.4 to 881.5 for Fe, 144 to 240 for Zn, 132 to 318 for Cu, 10 to 30 for Cd and 114.3 to 263 for Pb. Among these values only Cd concentrations considerably exceeded WHO guideline value (10 μg/L).